Adaptive Capacity and Inclusive Development Results of the OECD Development Centre 2003-2004 Programme of Work - Hiemenz, Ulrich (OECD Publishing, 2005)
The Centre has highlighted in particular four areas where OECD countries can make a difference: maintaining a stable macroeconomic environment with affordable interest rates; helping to mitigate risks; enhancing trade opportunities through improving the coherence of their own policies ;and increasing financial flows for achieving the MDGs
Keywords: Development